2010
DOI: 10.1163/157075610x523288
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of prey consumption by Liolaemus barbarae, a highland lizard endemic to Northern Chile

Abstract: Liolaemus barbarae is a small liolaemid lizard (SVL: 56 mm) endemic to the high Andes of northern Chile. Diet and prey availability were assessed during three seasons of activity (spring 2003, summer 2004, autumn 2004) in order to determine patterns of prey consumption and eventual selection. Liolaemus barbarae was strictly insectivorous preying on fl ying and epigeous insects, mainly chinch bugs (Lygaeidae) and ants. Prey types were consumed in diff erent proportions than available in the environment. Th e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Clearly, both OTU and family richness vary across populations likely in response to the distinct faunistic and floristic characteristics of these localities (Figure 1; [58]), which in turn determine the prey items available that can potentially be consumed by T. dugesii. Nevertheless, previous studies on both herbivorous and omnivorous lizards have shown the contribution of prey selection to diet composition, mostly according to nutrient requirements and avoidance of plant toxic compounds (e.g., [7,[86][87][88]). Water content was also reported as the most relevant factor for prey selection in the herbivorous lizard Liolaemus lutzae [89].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, both OTU and family richness vary across populations likely in response to the distinct faunistic and floristic characteristics of these localities (Figure 1; [58]), which in turn determine the prey items available that can potentially be consumed by T. dugesii. Nevertheless, previous studies on both herbivorous and omnivorous lizards have shown the contribution of prey selection to diet composition, mostly according to nutrient requirements and avoidance of plant toxic compounds (e.g., [7,[86][87][88]). Water content was also reported as the most relevant factor for prey selection in the herbivorous lizard Liolaemus lutzae [89].…”
Section: Discussionmentioning
confidence: 99%
“…también una presa fundamental para L. annectens. Esto coincide con otras especies de Liolaemus, como lo observado por Llanqui et al (2022) en la dieta de L. etheridgei en dos bosques de queñua (Polylepis rugulosa) en la zona andina de Arequipa, así como también en L. barbareae en Chile (Mella et al 2010). El mayor consumo de Lygaeidae podría estar asociado con su abundancia y dominancia en el hábitat, lo que la convierte en una presa común y de fácil captura (Llanqui et al 2022).…”
Section: Discussionunclassified
“…El mayor consumo de Lygaeidae podría estar asociado con su abundancia y dominancia en el hábitat, lo que la convierte en una presa común y de fácil captura (Llanqui et al 2022). También es posible que el mayor consumo de Lygaeidae se relacione con el tipo de alimentación del insecto (semillas y savia) y su comportamiento gregario, que reducirían los costos de búsqueda de presas (Mella et al 2010, Burdfield-Steel y Shuker 2014.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, Formicidae was avoided by L. etheridgei and seems not to be an essential prey for this lizard. Interestingly, Mella et al (2010) reported the avoidance of Formicidae and a positive selection for Lygaeidae in L. puna (= L. barbarae ), although plant material was not found in the diet as it was in L. etheridgei . It is worth noting that L. etheridgei belongs to the Eulaemus subgenus while L. puna (= barbarae ) belongs to the Liolaemus subgenus (Lobo et al, 2010), so this could be a case of ecological convergence.…”
Section: Discussionmentioning
confidence: 99%